2007
DOI: 10.1111/j.1524-4733.2006.00162.x
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life Measured with EQ-5D in Patients Treated for Depression in Primary Care

Abstract: Depression has a substantial impact on HRQL. Our results indicate that treatments for depression are associated with significant improvement in EQ-5D index score over a course of 6 months. Self-reported patient valuations are important outcomes for cost-utility analysis of new treatments for depression and the present study provides important evidence for future economic evaluations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
94
3
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(128 citation statements)
references
References 22 publications
26
94
3
5
Order By: Relevance
“…Six studies 139,142,144,[147][148][149] investigated the known-group validity of the EQ-5D across severity groups, five studies 129,136,137,143,145 reported convergent validity of the EQ-5D and 14 studies 50,[130][131][132][133][134][135][136][137][138]140,141,145,146 investigated the responsiveness of the EQ-5D. Two studies 139,142 had known-groups differences in the SF-6D, three 132,134,137 had convergent validity and two 136,145 had responsiveness.…”
Section: Depression and Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies 139,142,144,[147][148][149] investigated the known-group validity of the EQ-5D across severity groups, five studies 129,136,137,143,145 reported convergent validity of the EQ-5D and 14 studies 50,[130][131][132][133][134][135][136][137][138]140,141,145,146 investigated the responsiveness of the EQ-5D. Two studies 139,142 had known-groups differences in the SF-6D, three 132,134,137 had convergent validity and two 136,145 had responsiveness.…”
Section: Depression and Anxietymentioning
confidence: 99%
“…In all, there were 22 studies 50, identified with data on the validity and/or responsiveness of the generic HRQoL measures in depression and anxiety for EQ-5D and SF-6D. Fourteen studies 50,129,[136][137][138][139][142][143][144][145][146][147][148][149] had data on the EQ-5D and seven 130,131,[133][134][135]140,141 contained data on the SF-6D. Studies were undertaken in at least 12 countries (a number covered Europe).…”
Section: Depression and Anxietymentioning
confidence: 99%
“…The EQ-5D has been validated in UK populations and has been used to measure HRQoL in patients with depression in primary care. [49][50][51] Resource use data Information relating to participants' resource utilisation was obtained via two measures: completion of a self-report questionnaire (an adapted CSRI) and objective data collection from GP medical records.…”
mentioning
confidence: 99%
“…Depression is related to an impaired quality of life and ability to engage in social interactions, interpersonal relationships, and activities of independent living [30]. It is believed that depression is often caused by the influence of more than a single factor [31].…”
Section: Clinical Manifestations Of Depression In Caregiversmentioning
confidence: 99%